PENGARUH DAUN UBI JALAR UNGU TERHADAP PENINGKATAN KADAR HAEMOGLOBIN PADA IBU HAMIL DI KLINIK CINDY TAHUN 2025 - sihaloho, wilfa muslimah; Krisna, Putri; Insani, Septa Dwi; Samosir, Tiona Sampri (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2025)
Pregnancy-related anemia represents a significant contributor to maternal mortality in Indonesia.Haemoglobin is pregnant women affects fetal growth and development. Pregnant women need higher nutrition than women who are not pregnant because malnutrition during pregnancy can cause iron deficiency anemia, low birth weight babies and birth defects. Iron is very important this increase is attributed to the maternal blood volume expanding by 25% during gestation. Purple sweet potato leaves in every 100 gram’s , carotene 2700 μg, calcium 75- 183 mg, iron 1,8 – 3,9 mg, riboflavin 0,35 mg, and ascrorbic acid 32 – 136 mg ( Motsa,2015). Sweet potato leaves contain 47 kilocalories of energy, 2,8 gram’s protein, 10,4 gram’s carbohydrates, 0,4 gram fat, 79 miligrams calcium, 66 miligrams phosphorus and 10 miligram of iron. In addition, sweet potato leaves also contain 6016 IU of vitamin A, 0,12 miligram’s of vitamin B1 and 22 miligram’s of vitamin C. The presence of vitamin C enhances the absorption of non-heme iron by a factor of four because vitamin C plays a role in transferring iron from ransferin in plasma to fereitin in the liver, the process of forming haemoglobin and helping patossium absorption by keeping potassium in solution form. A Static Group Comparison methodology, employing a two-group pre-test and post-test framework, was utilized in this investigation. The study encompassed a research population of 47 individuals, with a sample size of 32 participants. Findings from this research reveal that the mean score prior to the administration of sweet potato leaves was 8.88 (standard deviation = 1.360), and the mean score subsequent to the administration of sweet potato leaves was 10.19 (standard deviation = 1.223), with a significance value of less than 0.05. In conclusion, this study demonstrates the impact of sweet potato leaves (Ipomoea Batatas) on the hemoglobin levels of pregnant women at the Cindy clinic in 2025.